ANALISIS CURAHAN WAKTU KERJA WANITA PADA USAHATANI JAGUNG MANIS DI DESA RASAU JAYA 2 KABUPATEN KUBU RAYA KALIMANTAN BARAT - PARWANTO, TEGUH; SUDRAJAT, JAJAT; HIDAYAT, RAKHMAD (Jurnal Sains Mahasiswa Pertanian, 2018)
ABSTRACT The agricultural sector in Indonesia is very important in development that is as a source of life and income of farmers in the family. Therefore, efforts to increase production and increase in farmers income need to be developed continuously. This research is aimed to analyze the working hours of women farmers work time and aimed to analyze socio-economic factors that influence the working hours of women farmers work time in sweet corn farming in Rasau Jaya II Village of Kubu Raya Regency. The sampling technique used is simple random sampling method. The sample used in this study amounted to 60 female farmers. This research uses Cobb - Douglas analysis, data processed using version 21 of SPSS program then analyzed by using multiple linear regression method. The results showed that age, land area, family income, and experience significantly affect the outpouring of female farmers work time, while the dependents of the family and the level of education did not significantly affect the working hours of women farmers work time in sweet corn farming in Rasau Jaya II Village of Kubu Raya Regency.Keyword : Cobb – Douglas, multiple linear regression, the working hours of women farmers Work Time